2013
DOI: 10.21273/horttech.23.3.382
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Tolerance to Phytophthora Blight of Bell Pepper Varieties

Abstract: In 2011, total marketable yield, fruit size, and number of lobes; fruit discoloration due to silvering; and plant structure were compared among eight commercial green bell pepper (Capsicum annuum) varieties and four breeding lines at three field sites in central New York. Tolerance to phytophthora blight (Phytophthora capsici) was also assessed at one of these sites. No wilting or plant death due to phytophthora blight was observed on the four breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…The isolate was periodically inoculated onto a host in the greenhouse and re-isolated in order to maintain virulence. Each year, peppers were inoculated multiple times (Table 2), and inoculum was prepared as previously described (6). In the first years of the trial, plants were inoculated later in the season and with lower concentrations of zoospores at early inoculation dates (Table 2).…”
Section: Inoculation With Phytophthora Capsicimentioning
confidence: 99%
“…The isolate was periodically inoculated onto a host in the greenhouse and re-isolated in order to maintain virulence. Each year, peppers were inoculated multiple times (Table 2), and inoculum was prepared as previously described (6). In the first years of the trial, plants were inoculated later in the season and with lower concentrations of zoospores at early inoculation dates (Table 2).…”
Section: Inoculation With Phytophthora Capsicimentioning
confidence: 99%
“…Nine new bell pepper inbred lines with excellent resistance to P. capsici have been developed. Four of these lines were previously evaluated for disease resistance and green bell pepper yield (Dunn et al, 2013). In this study, the disease screening data from the full set of PR lines is reported.…”
Section: Discussionmentioning
confidence: 99%
“…Each plot consisted of 10 plants and plants were spaced 18 inches apart in a single row. Inoculation and data collection procedures were as described in Dunn et al (2013). Briefly, a New York isolate of P. capsici (NY 066-4, collected from a bell pepper on a commercial vegetable farm in central New York in 2006; Dunn et al, 2010) was used to inoculate bell peppers 2, 4, and 6 weeks after transplanting in 2011.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations